STRATEGI BERTAHAN HIDUP PETANI KELAPA SAWIT TERHADAP KEGIATAN REPLANTING KELAPA SAWIT DI DESA BANJAR PANJANG KECAMATAN KERUMUTAN KABUPATEN PELALAWAN - Melati Citra Dewi; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The implementation of replanting activities causes the economic condition of farmers to be less stable so that the needs of the farmer’s families are not optimally met. This study aims to determine the economic conditions of oil palm farmers and also to determine the survival strategies of oil palm farmers against oil palm replanting activities in Banjar Panjang Village, Kerumutan District, Pelalawan Regency. This type of research use descriptive analysis with a quantitative approach. The total population in this study were 245 oil palm farmers who carried out replanting. Sampling used in this study is a simple random sampling technique using the Taro Yamane formula totaling 71 oil palm farmers. The results of the study at the time of oil palm replanting took place, the survival strategy that was mostly applied by respondents was a passive strategy, then an active strategy, and the least was a network strategy. Keywords: Replanting, Economic Condition, Farmer Survival Strategy